Spatiotemporal characteristics of present-day horizontal deformation of the Yishu Fault Zone in Shandong, China - Bin Yang; Hongbin Wu; Sili Su; Hongtai Xu; Tengchao Dong; Fugang Ge (Geocarto International)
The Yishu Fault Zone in eastern China poses a significant seismic hazard, yet its current deformation characteristics are not well-understood. This study investigates the Ju County-Tancheng section, notable for diverse terrain and significant historical earthquakes, including the 70 BC Anqiu M7 and the 1668 Tancheng M8.5 events. Combining fieldwork, trenching, and LiDAR technology, we examined horizontal displacement from January 2020 to December 2021. Observations at 63 sites across the Zuoshan and Zhonghuashan segments revealed significant right-lateral and thrust faulting, confirmed by stratigraphic evidence. Integrating LiDAR with Variational Mode Decomposition (VMD) analysis highlighted the temporal characteristics of crustal deformation. Results show that fault activity involves right-lateral strike-slip and thrusting, with average displacement rates of 2.57 mm/year and thrusting rates of 3.1 mm/year. This study underscores the innovative use of LiDAR and VMD techniques, offering high-precision data and enhancing geological interpretation for improved seismic prediction and risk assessment.